A preliminary catalogue of the Coleoptera (Hexapoda: Insecta) of the Monte Netto Regional Park (Lombardy NE Italy) - Mola, Livio; Ruzzier, Enrico; Deiaco, Claudio; Agosti, Mauro; Faccoli, Massimo; Matějíček, Jan; Farina, Laura; Diotti, Luciano; Rocca, Francesca Della (Zootaxa, 2023)
The Po Plain (Northern Italy) is one of the most urbanized areas in Europe. In such a territory, where ecosystem degradation reached critical levels and the agricultural matrix is prevailingly intensive, small fragments of hilly oak-hornbeam forests still persist. Examples of well preserved forests of the Po Plain are those of the Monte Netto Regional Park that represents irreplaceable refuges for both sedentary and migratory species. In this paper we present a preliminary list of Coleoptera inhabiting the Park collected during 10 years of field surveys using several sampling techniques (hand netting, beating tray, sight-collecting and collecting under bark; water nets; litter reducers, light traps; aerial sweet-bait trap; cross-vane panel trap, pitfall traps, Malaise traps, window traps, and walking transects). Specific samplings were also made in tree hollows and by car-netting. To date we have identified 834 species belonging to 531 genera and 71 families (several specimens and some families are still undetermined). Among all the species identified, 31 were non-native while 202 were included in the Red List of Italian saproxylic beetles, 12 of which were in threatened category. The high beetle richness and the presence of many endangered species recorded during this survey, emphasises the conservation value of Monte Netto. Moreover, the discovery of species linked to old and stable forest systems, such as Osmoderma eremita, Oxylaemus cylindricus, Pycnomerus terebrans or Xylotrechus antilope suggests how, despite their small size and the fact that they are surrounded by agricultural land, the remaining forest patches of Monte Netto still possess a fair level of naturalness, especially in the internal areas of the larger plots. Future targeted research, also intended to cover other parts of Monte Netto, could increase our present knowledge; however, and at least in the number of families, we do not expect a substantial increase in species richness.